STRATEGI EKONOMI MASYARAKAT PASCAPERENCANAAN PEMBANGUNAN KAMPUS INSTITUT TEKNOLOGI SUMATERA (Studi tentang Perubahan Sosial di Desa Sabah Balau, Kecamatan Tanjung Bintang, Kabupaten Lampung Selatan) - Fahrurozi Saputra; Erna Rochana (SOSIOLOGI: Jurnal Ilmiah Kajian Ilmu Sosial dan Budaya, 2014)
This research purposed to explore information about the community's economic strategy in Desa Sabah Balau Kecamatan Tanjung Bintang Kabupaten Lampung Selatan postplanning Sumatera Institute of Technology (ITERA). Development situation exploited by high society owners of capital to boost the economy. On the other hand, do the poor economic strategy by seeking to survive in order not marginalized, as predicted Desa Sabah Balau will experience significant social change. The results showed that the public response is very open and accepting ITERA development, because it sure will bring significant changes to the village. Citizens from all walks of life have prepared strategies include: for the people who have the capital they (1) sell the land to exploit the situation ITERA development, (2) sell the land when land prices rise, (3) save the land for their own business, and (4) began to build a place of business. Poor people who do not have the capital assets such as land or other personal attempt to (1) look for another job, because it is no longer working as casual laborers in PTPN VII, (2) submit the ability to work in construction as a bricklayer ITERA to stakeholders; (3) involve family members to work, and (4) reducing the need to tighten spending.